FREQUENCY AND CORRELATION OF MOLECULAR SUBTYPES OF BREAST CANCER WITH CLINICOPATHOLOGICAL FEATURES - Akbar, Mohammad; Akbar, Kehkashan; Naveed, Danish (Journal of Ayub Medical College Abbottabad, 2014)
Background: Traditional clinicopathological classification of breast cancer has limitations as tumours with similar clinical and histological features behave differently regarding outcome and responsiveness to chemo/immunotherapy. The objectives of the study were to determine the frequency of different molecular subtypes of breast cancer based on immunohistochemical staining and to find the correlation of each subtype with clinicopathological features. Methods: Sixty patients with histologically diagnosed invasive ductal carcinoma were enrolled in this cross sectional study. Immunohistological staining of the tumour samples and based on receptor status tumours were classified in four subtypes, Luminal A, Luminal B, HER2/neu oncogene amplification subtype and Tripple negative subtype. Clinical features, stage of disease at presentation and histopathological grade of the tumours was also recoded in each subtype. Prevalence of each subtype was calculated and correlation with clinical and pathological features was determined. Results: Mean age of the patients was 47.55 years. Protective role of breast feeding was not confirmed in this study as 58 (96.67%) patients breast fed their children. Only two (3.33%) patients gave family history of breast cancer in the study. Thirty three (55%) patients had grade 2 tumours, 26 (43.33%) had grade 3 tumours while only one patient had grade 1 tumour. HER2/neu amplification subtype was the most common molecular subclass in the study, comprising 30% of all the patients. Ten patients (16.67%) in this study belonged to triple negative group. Triple negative disease was found in younger women with mean age of 40-60 years. Conclusion: Breast cancer particularly triple negative disease was found in younger age group and patients usually present in advanced stage of their disease.HER2/neu positive breast cancer was the most common subtype in this study. Keywords: Oestrogen receptors, Progesterone receptors, Molicular Targeted therapy, Gene expression profiling, microarray analysis, Fluorescence, in situ hybridization